Strategi Pemasaran G-Coffee Menggunakan Analisis SWOT Guna Menghadapi Era Society 5.0 - Fandy Bestario Harlan; Yulinda Tarigan; Atiqotun Nisa (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
Increasing the number of residents in the city of Batam is a strategic goal in developing an entrepreneurial and business climate. This is in line with the development of micro, small and medium enterprises in Batam City. The purpose of this study is to analyze the needs for culinary tourism that are in demand by the community, especially millennials in Batam City. G-Coffee is a culinary tourism object that has a place with a contemporary design. The method used in this research is descriptive qualitative which aims to dig up information about Digital marketing management at G-Coffee for the needs of the community in terms of culinary tourism, this will later increase competitiveness and a wider market in its marketing strategy to face the era of society 5.0 where digital transformation has changed various habits and ways of life of society and industry including realizing Digital MSMEs. Based on research results, currently G-Coffee is very strong in the use of social media, especially to attract their customer segment which consists of students and students. In the future there needs to be a specific strategy that needs to be developed so that G-Coffe can still compete with its competitors.